The Immigrant World of Ybor City: Italians and Their Latin Neighbors in Tampa, 1880-1980 - Iacovetta, Franca (Labour / Le Travail, 1989)
The article reviews the book, "The Immigrant World of Ybor City: Italians and Their Latin Neighbors in Tampa, 1880-1980," by Gary R. Mormino and George E. Pozzetta.
Keywords: IMMIGRANT World of Ybor City: Italians & Their Latin Neighbors in Tampa 1880-1980 (Book); Immigrants; MORMINO; Gary R.; Nonfiction; POZZETTA; George E.; REVIEWS; books